MONITORING DAN EVALUASI PENERAPAN STANDAR MUTU PERENCANAAN, PELAKSANAAN DAN PEMELIHARAAN JALAN KABUPATEN MOROWALI - , DESTUBER MATO ORI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The main cause of the problem in structural damage of local roads lies on the disobedience in applying Standard, Guidelines, and Manual (SGM/ SPM), thus it negatively affects the performance of local road technical services, it occurs even before the determined longevity of roads reached. We find many early damages on the paved roads, and we make an assumption that the cause of the condition is construction failures. Regency of Morowali has a long way to go about 1015,6 km, in a damaged condition (heavy, mediun anda light). Research on monitoring and evaluation of the implementation of quality standards is important to be done to determine the level of difficulty, the application of quality standards and implementation constraints. Data obtained by filling out the questionnaire, using Likert scale with a closed question. Monitoring and evaluation should be conducted systemically by belonging, understanding, applying, and controlling the application of Indonesian National Standard (SNI). Assessing the factor and variable is conducted through the scoring system with rate counting. Experiment in monitoring and evaluation in the application of SNI (National Standard) 03-1732-1989 (manual/guides for planning of the paving thickness of flexible pavement through component analysis method), SNI 03-2853-1992 (manual for the implementation of foundation pavement coating with coral stone) and SNI 03-3979-1995 (manual for the process of single layer asphalt coating for the surface of road) in the management of road system in the Regency of Morowali. The results of the study show that the cognition level of respondents to these three of SNIâs is relatively low. Only 43.24% of respondents know the first SNI, 40.08% of respondents recognize the second SNI, and only 38.58% of respondent comprehend the third SNI, it means that the accessibility level of information is still relatively low. The understanding to the languages and substances of the three SNI is optimal, 67.47% respondents understand the languages and substances of first SNI, 65.47% of respondents understand the languages and substances of second SNI, and 67.33% of respondent understand the language and substance of the third one, it means that these three SNI is easily understandable for roads staffs in Regency of Morowali. The level of application of these three SNI is generally simply optimal, the first SNI is applicable for 63.25% of respondents, the second SNI is applicable for 60.33% of respondents and the third one is applicable for 59.73% of respondents, this fact shows that the applicability of each SNI is relatively optimal. The main obstacle in the implementation of quality standards is ineffective controlling in quality guarantying.